PET‐adapted therapy after three cycles of ABVD for all stages of Hodgkin lymphoma: results of the GATLA LH‐05 trial. (12th March 2019) - Pavlovsky, Astrid; Fernandez, Isolda; Kurgansky, Nicolas; Prates, Virginia; Zoppegno, Lucia; Negri, Pedro; Milone, Gustavo; Cerutti, Ider; Zabaljauregui, Soledad; Mariano, Romina; Grecco, Horacio F.; Basquiera, Ana L.; et al.
Summary: The role of Ann Arbor staging in determining treatment intensity after achieving a negative positron emission tomography (PET) has not been established in classical Hodgkin lymphoma (cHL). Patients with stage I–IV cHL, received three cycles of ABVD (doxorubicin, bleomycin, vinblastine, dacarbazine) and an interim PET scan (PET3). PET3‐negative patients received no further therapy. PET3‐positive patients received three additional cycles of ABVD plus involved‐field radiation therapy or salvage chemotherapy, if refractory to ABVD, and were re‐evaluated by PET scan (PET6). Study endpoints were 3‐year progression‐free survival (PFS) and overall survival (OS) rates. Two hundred and thirty‐nine patients with early‐stage and 138 with advanced‐stage were evaluable. Overall, 260 patients (70%) were PET3‐negative and had higher 3‐year PFS (90% vs. 65%; P < 0·0001) and OS (98% vs. 92%; P = 0·007) rates than PET3‐positive patients. All PET3‐negative patients, regardless of disease stage at diagnosis, achieved similarly good PFS (90–91%; P = 0·76) and OS (97–99%). The only independent prognostic factor for PFS was PET3‐negativity (Hazard ratio 3·8; 95% confidence interval 2·4–6·3; P < 0·0001). This study suggests that cHL patients who achieve a negative PET3 following ABVD have an excellent outcome, regardless of stage at diagnosis. An appropriately powered, phase III trial will be necessary to confirm these findings.